Caregiver Burden and its Psychosocial Correlates among Caregivers of Traumatic Spinal Cord Injury Survivors in Pakistan - Neelam Bibi,; Naeem Aslam, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Caring for someone with a spinal cord injury (SCI) has always been a family endeavor in developed as well as developing countries like Pakistan. The majority of people with SCI need assistance from others to carry out daily life activities, i.e., eating, self care, transportation, etc., and this functional dependence of the patient on their attendant affects the Quality of Life (QOL) of caregivers. Aim: To find the relationship between caregiver burden, psychosocial factors, and QOL among caregivers. Methods: A cross-sectional research design with purposive sampling technique was used to gather data from spinal units of various hospitals in Pakistan. Caregiver Burden Inventory (SCI) and WHOQOL were used to measure study variables. Sample size includes 255 family caregivers of SCI patients. Correlation analyses were applied to find the relationship between psychosocial factors, caregiver burden, and QOL. Results: Results showed that caregiver burden was significantly negatively correlated with quality of life and positively correlated with caregiving hours, duration of injury, and number of helpers involved in the caregiving process. Furthermore, female caregivers showed high levels of caregiver burden and low levels of quality of life as compared to their male counterparts. Similarly, married persons scored higher on caregiver burden and whose patients had paraplegic nature of injury. Conclusion: In Pakistan, there are no respite care programs for caregivers. The abovementioned findings are helpful in planning psychotherapeutic interventions and tailored caregiver training programs to lessen the impact of caregiver burden on caregivers and to boost their quality of life. Keywords: Caregivers, caregiver burden, functional dependence, psychosocial factors, quality of life